2004
DOI: 10.1016/j.cogsci.2003.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation-based processing: a unified theory of semantic sentence comprehension

Abstract: We present interpretation-based processing-a theory of sentence processing that builds a syntactic and a semantic representation for a sentence and assigns an interpretation to the sentence as soon as possible. That interpretation can further participate in comprehension and in lexical processing and is vital for relating the sentence to the prior discourse. Our theory offers a unified account of the processing of literal sentences, metaphoric sentences, and sentences containing semantic illusions. It also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It should be possible to extend the model to lower levels of processing to explore the interactions of lexical and syntactic processing; indeed much of the structure is already in place to do so. It should also be possible to extend the model to higher levels of semantic and discourse processing; an integration with the semantic interpretation model of Budiu and Anderson (2004) provides one possible avenue. Given prior ACT-R work on modeling in-dividual differences, it should also be possible to use this model as a basis for accounting for performance differences due to variation in working-memory capacity.…”
Section: The Value Of Architectures and Prospects For The Futurementioning
confidence: 99%
“…It should be possible to extend the model to lower levels of processing to explore the interactions of lexical and syntactic processing; indeed much of the structure is already in place to do so. It should also be possible to extend the model to higher levels of semantic and discourse processing; an integration with the semantic interpretation model of Budiu and Anderson (2004) provides one possible avenue. Given prior ACT-R work on modeling in-dividual differences, it should also be possible to use this model as a basis for accounting for performance differences due to variation in working-memory capacity.…”
Section: The Value Of Architectures and Prospects For The Futurementioning
confidence: 99%
“…In search over text, the semantics of an item signals its potential value relative to the goal of the search (here item refers to images, text, or other visual objects). Cognitive models instantiate searchers' relevance judgments using prior measures of semantic association between a label for the information goal and the items of interest (Budiu & Anderson, ). In modeling, the strength of the association determines the spread of activation in memory to knowledge about the item (Brumby & Howes, , ; Fu & Pirolli, ; Teo & John, ).…”
Section: Related Workmentioning
confidence: 99%
“…This hypothesis is supported by Levie and Lentz (1982), who have shown that information is remembered and retrieved better when accompanied by relevant pictures. More precisely, Budiu and Anderson (2004) demonstrated that users can use a rich sentence context to arrive at the meaning of an ambiguous word. Another supporting piece of research is based on construction-integration theory of text comprehension (Kintsch 1998), which explains that the incoming text element, the previously read text, the user goal, and the user background knowledge determine, in this order of priority, which concepts are activated at any given point of time.…”
Section: Colides þ Picmentioning
confidence: 98%